Transformasi Ekonomi Melalui Piala Dunia FIFA 2022: Analisis Meningkatnya Pendapatan Per Kapita di Qatar sebagai Tuan Rumah - Aqila Chairunnisa, Gina; Muhammad Muchlis, Madian (CV. Lafadz Jaya, 2023)
The FIFA World Cup in Qatar is a prestigious sporting event, providing a unique opportunity for the country to gain economic benefits and increase Per Capita Income (PPK). This research aims to explore the impact of holding the World Cup on Qatar's PPK, by focusing on infrastructure development, economic investment and its long-term effects. This research uses descriptive design and comparative analysis with quantitative and qualitative approaches. Economic and infrastructure data is collected from official institutions and Qatari government authorities. Regression analysis is used to identify the relationship between independent variables (infrastructure development, economic investment) and the dependent variable (Income Per Capita). The research findings show that Qatar experienced a significant increase in Per Capita Income during and after the 2022 World Cup. The construction of modern stadiums, expansion of transport infrastructure and World Cup-related economic investments served as key drivers of the increase. This research concludes that holding the 2022 FIFA World Cup has a positive impact on Qatar's Per Capita Income, opening the door for learning and economic development strategies in the future. The implications of the research findings can provide guidance for other countries planning to host similar international sporting events.